Powstawanie Kościoła: od eklezjogenezy chrystocentrycznej do eklezjogenezy trynitarnej - Napiórkowski, Andrzej (Verbum Vitae, 2023)
In the post-conciliar period, there has been a significant development in the doctrine of the Church, in which it is necessary to distinguish between what is permanently current and what is changeable and historical. This means that the sources of Revelation do not change, but our understanding of them develops. As we delve into the mystery of the Church, we need to grasp both its constant change and the changing of its understanding. Therefore, the great achievements of biblical, patristic, and other sciences in the nineteenth and twentieth centuries impel to a revision of the existing image of the Church. The aim of this article is to show the close connection between the Old Testament’s and the New Testament’s Revelation to draw more from biblical Judaism. It is also necessary to discover the richness of patristic thought and approach the heritage of the East with ecumenical sensitivity. Therefore, the ecclesiogenesis presented in the article consists of five stages of the Church formation. These premises bring a lot of stimulating inspiration to a new understanding of God and man. It is an oversimplification to speak of the Church by reducing it merely to God. Nor is there an ecclesiastical reality without human beings although people themselves, even those baptized, are not yet the Church. Both realities – divine and human – build up the Ecclesia together. Hence – without losing sight of ecclesiastical theandry – it should be remembered that the divine-human community is a reality that constantly becomes and is full of salvific dynamism. And just as the post-conciliar ecclesiology departed from the claim that Jesus Christ founded the Church, so today it takes the next step and makes an effort to move away from reducing the Church to a Christocentric aspect only, to see it more as a Trinitarian one.